2021
DOI: 10.1029/2021ja029516
|View full text |Cite
|
Sign up to set email alerts
|

Hot Plasma in the Magnetotail Lobes Shows Characteristics Consistent With Closed Field Lines Trapped in the Lobes

Abstract: We examine the magnetotail using data from the Hot Ion Analyzer on Cluster 1 during 2001–2009. We develop and utilize an algorithm in order to identify times during which Cluster 1 is in the magnetotail lobe but observes plasma, which is hotter than our expectations of the lobe. We analyze the prevailing Interplanetary Magnetic Field (IMF) BZ conditions for our algorithm and a reference algorithm (with no particle energy criteria) and find that the periods we select are, on average, 00∼2 nT more toward northwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 57 publications
4
6
0
Order By: Relevance
“…Coxon et al. (2021) recently showed that hot plasma consistent with trapping on closed field lines is frequently seen at | Z | > 5 R E during northward IMF; here we have shown that CAAs are the auroral signature of this closed flux, and that at such times the magnetosphere is likely (almost) entirely closed. We believe that this closure is achieved by DLR, as proposed by Milan, Carter, Bower, et al.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Coxon et al. (2021) recently showed that hot plasma consistent with trapping on closed field lines is frequently seen at | Z | > 5 R E during northward IMF; here we have shown that CAAs are the auroral signature of this closed flux, and that at such times the magnetosphere is likely (almost) entirely closed. We believe that this closure is achieved by DLR, as proposed by Milan, Carter, Bower, et al.…”
Section: Discussionsupporting
confidence: 73%
“…This trapped plasma will provide a source for the CAA auroral emission, and as the auroral emission (and associated precipitation) covered the polar regions, we further suggest that the magnetosphere was almost entirely closed. Coxon et al (2021) recently showed that hot plasma consistent with trapping on closed field lines is frequently seen at |Z| > 5 R E during northward IMF; here we have shown that CAAs are the auroral signature of this closed flux, and that at such times the magnetosphere is likely (almost) entirely closed. We believe that this closure is achieved by DLR, as proposed by Milan, Carter, Bower, et al (2020) and Milan et al (2022).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…(2021), and Coxon et al. (2021). However, the configuration we observe in this simulation differs from that proposed by Milan et al.…”
Section: Discussionmentioning
confidence: 97%
“…(2021) and Coxon et al. (2021). Therefore, in this study, we compare the output of the GUMICS model under varying northward IMF conditions with the characteristics that have been previously observed based on the Milan et al.…”
Section: Introductionmentioning
confidence: 96%